2021
DOI: 10.3389/fmicb.2021.604567
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Ciprofloxacin and Ceftazidime-Resistant Enterobacterales From Vegetables and River Water Is Strongly Associated With the Season and the Sample Type

Abstract: The dissemination of antibiotic-resistant bacteria (ARB) from water used for crop irrigation to vegetables is poorly studied. During a year, five farmer markets in a city in Central Chile were visited, and 478 vegetable samples (parsleys, corianders, celeries, lettuces, chards, and beets) were collected. Simultaneously, 32 water samples were collected from two rivers which are used to irrigate the vegetables produced in the area. Resistant Enterobacterales were isolated and identified. Colistin resistance gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 52 publications
0
9
0
1
Order By: Relevance
“…However, in this study all the ESBL-producing E. coli were isolated during the summer or early autumn when rainfall was low. Previous studies have found a higher prevalence of third-generation cephalosporin-resistant E. coli in autumn [18,54].…”
Section: Summary Of Sample Sitesmentioning
confidence: 77%
See 1 more Smart Citation
“…However, in this study all the ESBL-producing E. coli were isolated during the summer or early autumn when rainfall was low. Previous studies have found a higher prevalence of third-generation cephalosporin-resistant E. coli in autumn [18,54].…”
Section: Summary Of Sample Sitesmentioning
confidence: 77%
“…Previous studies have found a higher prevalence of third-generation cephalosporin-resistant E. coli in autumn [18, 54].…”
Section: Resultsmentioning
confidence: 99%
“…More generally, for a plasmid copy number p the number of replications of the plasmid expected for a given number of cell generations g will be p x g (assuming that plasmid copies are simply and linearly related to the realised number of replications per cell). A crude estimate for the expected mutation rate per time period for a plasmid is therefore given by L x m x p x g. For a plasmid of L=100 kbp and p=1, assuming m=[0.1-1]x10 -9 per site per generation and g= [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]x365 per year, one would expect it to accumulate ~0.5 mutations a year (between ~0.02-0.7 depending on assumptions). One obtains the same result for L=10 kbp and p=10.…”
Section: Plasmid Mutation Ratementioning
confidence: 99%
“…Chau 1 , Derrick W. Crook 1,6,7 , Nicola de Maio 1 , Nicholas Duggett 2 , Daniel J. Wilson 1,9 , Daniel Gilson 2 , H. Soon Gweon 3,4 , Alasdair Hubbard 10 , Sarah J. Hoosdally 1 , William…”
Section: Data Availabilitymentioning
confidence: 99%
See 1 more Smart Citation